Maritime ethics understanding morality in the tideline - Vilar, Rucelio P. (Jobal Publishing House, 2015)
"The purpose of this handbook is to orient student taking up maritime courses to understand the concepts of morality and ethical frameworks in very credible and feasible perspective. responsiveness to moral cases as applied in maritime discipline between the students or professionals involved is highlighted as it pertains to the principles used in day to day moral situation.